Building Java enterprise applications - McLaughlin, Brett (O'Reilly, 2002)
What are the key decisions and tradeoffs you face as you design and develop enterprise applications? How do you build the back end so that it not only handles your current needs but is flexible enough to allow your system to evolve as your needs expand? Answer these questions and many more with Building Java Enterprise Applications, an advanced guide to building complex Java Enterprise Applications from the ground up that addresses design issues along the way. These practical books take a step back from detailed examination of the APIs and focus on the entire picture, so you can put the pieces together and build something that works! This book explores the infrastructure issues so important to good application design. It isn't just a book about doing things with Entity Beans, JDBC and JMS and JNDI. It takes you step by step through building the back end, designing the data store so that it gives you convenient access to the data your application needs; designing a directory; figuring out how to handle security and where to store security credentials you need; and so on. On top of this, it shows -- as easily as possible --how to build the entity bean layer that makes information available to the rest of the application. Throughout this guide, author Brett McLaughlin uses his wealth of real-world experience with enterprise development to show you one step at a time how to design and build a comprehensive enterprise application from the ground up, starting with the back end.